Fresno County Bar Association Luncheon w/ Dr. John Garry and Hon. Ralph Moradian re Armenia - Watkins, Howard::::::::: (1989)
Dr. John Garry speaking at Fresno Hilton 2nd floor ballroom lectern; seated Fresno County Bar Association President G. Dana French On wall is Fresno County Bar Association Banner showing "Established 1882"